Mangrara Banua Tongkonan Ceremony For The Toraja Tribal Community In Akung Village - Riani Bunga Samma; Darman Manda (Gudang Jurnal Multidisiplin Ilmu, 2026)
This research examines the persistence of the Mangrara Banua Tongkonan ceremony in Akung Village through a cultural anthropology approach. As a sacred Torajan ritual, this traditional house consecration ceremony endures due to its deep cultural significance for the local community. Anthropological analysis reveals that Mangrara Banua is not merely a physical celebration of a new structure, but a cultural institution rich in symbolic meaning. First, the ritual serves as a collective expression of gratitude to God the Creator. Second, it functions to articulate and legitimize the family's social status (tana') within the community hierarchy. Third, this momentum acts as a unifying medium for the extended family (tongkonan) to reinforce kinship ties. Finally, the ritual embodies sacred reverence for the ancestors. Through an anthropological lens, the continuity of this tradition proves that the Tongkonan remains the cosmic, social, and spiritual center for the people of Akung Village amid modernization.